Linear Regression Model in Prediction System - P.Chandramoorthi (International Journal of Engineering and Management Research, 2019)
Linear regression is a statistical process for calculating the value of a dependent variable from an independent variable. Linear regression is a method to quantify the relationship between one or more predictor variables and a response variable. It is a modeling technique where a dependent variable is predicted based on one or more independent variables. Linear regression analysis is the most frequently used of all statistical techniques. This paper explains the basic concepts and explains the concept of Linear Regression in prediction system.